Combating Misinformation Through Nudging - Konstantinou, Loukas; Caraban, Ana; Karapanos, Evangelos (My University, 2019)
Recent studies have shown that the spread and consumption of misinformation online can be attributed to errors in human decision making, facilitated by cognitive biases. The field of Behavioral Economics has contributed a repertoire of such cognitive biases that can be leveraged for the design of technological interventions. In particular, the concept of nudging refers to subtle changes in the ‘choice architecture’ that can alter people’s behaviors in predictable ways. In this paper we present our ongoing work on the design of nudging interventions in the context of misinformation, including a systematic review of the use of nudging in HCI that has led to a design framework consisting of 23 mechanisms of nudging tapping to 15 different cognitive biases, the translation of this framework into a set of design cards, the Nudge Deck, and its use in a planned workshop that aims to explore the design space of misinformation in the context of nudging.
Keywords: Behavior change; Misinformation; Nudging